Evaluation of neurological behaviour in late‐preterm newborn infants using the Hammersmith Neonatal Neurological Examination. (21st September 2018) - Chin, En Yi Joanne; Baral, Vijay R; Ereno, Imelda L; Allen, John C; Low, Kelly; Yeo, Cheo Lian
Abstract : Aim: We hypothesise that clinically well late‐preterm infants (LPI) (34 +0 –36 +6 weeks) are neurologically more immature than their term counterparts, and this immaturity persists even when these infants reach term‐corrected age (TCA). The primary aim of our study was to characterise and contrast the neurodevelopmental profile of well LPI with full‐term infants (FTI) (39 +0 –41 +6 weeks) using the Hammersmith Neonatal Neurological Examination (HNNE). Our secondary aim was to obtain local reference ranges for the 34 items in the HNNE in an Asian‐dominant population. Methods: LPI were assessed at two time points: 12–72 h of life and at TCA of 39 +0 –41 +6 weeks, while FTI were assessed at 12–72 h of life using the HNNE. Each of the 34 items on the HNNE was assigned an optimality score (OS) of 0, 0.5 or 1, totalling up to 34. A quantitative comparison of the neurobehavioral patterns was made using two‐sample t ‐tests. Results: A total of 212 infants (79 LPI and 133 FTI) were recruited. Mean OSs for LPI and FTI at birth were (25.11 ± 3.36)/34 and (31.19 ± 1.50)/34, respectively, with a mean difference of 6.08 ( P value <0.0001). The mean OS for LPI on reaching TCA was (28.91 ± 2.30)/34, with a mean difference of 2.28 ( P value <0.0001). Reference OSs for the 34 items on the HNNE were also obtained. Conclusion: LPI are more immature than their term counterparts even on reaching TCA, with discrepancies most apparent in 'tone' and 'movement'. We provide reference OSs of 34 items in the HNNE for infants in an Asian‐dominant population.